Subcutaneous versus intravenous bortezomib in two different induction therapies for newly diagnosed multiple myeloma: an interim analysis from the prospective GMMG-MM5 trial - Merz, Maximilian; Mai, Elias K.; Bertsch, Uta; Hose, Dirk; Seckinger, Anja; Jauch, Anna; Hillengaß, Jens; Raab, Marc-Steffen; Schurich, Bärbel; Goldschmidt, Hartmut (Haematologica, 2015)
We investigated the impact of subcutaneous versus intravenous bortezomib in the MM5 trial of the German-Speaking Myeloma Multicenter Group which compared bortezomib, doxorubicin, and dexamethasone with bortezomib, cyclophosphamide, and dexamethasone induction therapy in newly diagnosed multiple myeloma. Based on data from relapsed myeloma, the route of administration for bortezomib was changed from intravenous to subcutaneous after 314 of 604 patients had been enrolled. We analyzed 598 patients who received at least one dose of trial medication. Adverse events were reported more frequently in patients treated with intravenous bortezomib (intravenous=65%; subcutaneous=56%, P=0.02). Rates of grade 2 or more peripheral neuropathy were higher in patients treated with intravenous bortezomib during the third cycle (intravenous=8%; subcutaneous=2%, P=0.001). Overall response rates were similar in patients treated intravenously or subcutaneously. The presence of International Staging System stage III disease, renal impairment or adverse cytogenetic abnormalities did not have a negative impact on overall response rates in either group. To our knowledge this is the largest study to present data comparing subcutaneous with intravenous bortezomib in newly diagnosed myeloma. We show better tolerance and similar overall response rates for subcutaneous compared to intravenous bortezomib. The clinical trial is registered at eudract.ema.europa.eu as n. 2010-019173-16.
Gesehen am 13.04.2017